Implementasi Program Beasiswa Banyuwangi Cerdas di Dinas Pendidikan Kabupaten Banyuwangi - Tegar Rifki Ardani (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes the implementation of the Banyuwangi Cerdas Scholarship (PBC) Program at the Banyuwangi Regency Education Office. This program aims to help high-achieving students from underprivileged families complete their higher education. The study used qualitative methods based on George C. Edward III's theory, which examines four main aspects: communication, resources, disposition, and bureaucratic structure. Data were collected through interviews, observation, and documentation. The results indicate that the program has been running well, but still faces several challenges. In terms of communication, dissemination has not been evenly distributed across all levels of society. In terms of resources, the budget and facilities are adequate, although implementing officers have not received special incentives. In terms of coordination, inter-sectoral coordination has been established, but fund disbursement times are often delayed. Overall, this program is effective in increasing access to education in Banyuwangi, but requires improvements to the information system and a reduction in funding disbursement time.
Finalisasi Rudy K_ 4 Agustus 2026
Keywords: Policy Implementation; PBC; Education Office.